Midwife Care On 3 Months Injected Kb Accepters With Spotting At The Angel Paropo Maternity Clinic - Ernita Ruslaini Caniago; Devi Susana Pinem; Tiurlina Monika Monik (Institute of Computer Science (IOCS), 2021)
Family planning is a government program that is planned to balance between needs and population. From the data obtained from the Angel Paropo Clinic, mothers who used contraception in February and March were 103 acceptors including 1 IUD KB, 2 implant KB, 35 KB 1 month injections, 45 3 Months KB injections and 20 KB Pills. person. Carry out midwifery care for 3 month injection contraceptive acceptors by spotting thoroughly using 7 steps of Varney's midwifery management. The method used is a case study. The location of this case study is at the Angel Paropo clinic. The subject of the case study is a 3-month injection contraceptive acceptor with spotting. The time of the case study is April 20-26, 2021. Data collection techniques from physical examination, interviews and observations, secondary data includes documentation studies and literature studies. The care provided in this case is the administration of combined contraceptive pills 2x1 (30-35 g ethinylestradiol for 7 days), ibuprofen (up to 800 mg, 3x/day for 5 days), moral support and vuva hygiene counseling. the result is that the general condition is good, there are no potential problems that arise, the mother is not anxious and feels comfortable, the bleeding stops, the mother is willing to come to the health facility if there are complaints and the mother continues to use injectable contraception for 3 months. After 7 days of midwifery care, the injection contraceptive acceptors no longer experienced spotting